Community Engagement In Urban Areas Of South Tangerang Regency, Indonesia: A Study On Covid-19 Response - Boerman, Baequni; Nasir, Narila Mutia (Jurnal Kesehatan Masyarakat, 2024)
In Indonesia, particularly in South Tangerang, Banten Province, high COVID-19 cases are intensified by urban density. A comprehensive study was initiated by 106 students from UIN Syarif Hidayatullah Jakarta. Employing a cross-sectional design with purposive sampling, they surveyed 5,326 households across 13 Community Health Centers. The Chi-Square tested data uncovered that 79% consistently wore masks, 74% practiced hand hygiene, 59% followed social distancing, and 37% regularly disinfected. Intriguingly, there’s a substantial correlation between protocol adherence and factors like knowledge, attitude, and proactive community leadership. These factors amplified adherence effectiveness between 2.0 to 3.5 times. The findings highlight the potential of the Community-Based Fighting Initiatives Against COVID-19 (PARC-19) approach, stressing grassroots engagement. Implementing PARC-19 successfully mandates fostering community autonomy in health management. Such autonomy flourishes when forged through a collaboration net comprising academia, government agencies, social organizations, influential community and religious leaders, and business stakeholders. This synergized effort paves the way for a holistic and efficient health management strategy during these pandemic times.